Innovation in Developing an Experiential Learning Model to Foster Creativity and Active Learning in Writing Drama Texts - Joni Pranata; Dzarna; Astri Widyaruli Anggraeni (Raja Zulkarnain Education Foundation, 2025)
This study aims to explore innovations in the development of experiential learning models to foster creativity and active learning in students. This study is based on the low participation and creativity of students in learning drama texts. This is due to the learning methods used by teachers who are still conventional and do not involve students enough, resulting in teacher-centered learning and minimal space for exploring ideas. Through the development in this study, students are invited to understand the theory and connect it with authentic experiences, thereby actively engaging in reflection, experimentation, and direct application activities. This study uses a classroom action research method that was carried out for two cycles and involved all students in class XI 6 SMAN Mumbulsari. Data collection was carried out through participatory observation, semi-structured interviews, document analysis, and creativity questionnaires. The results of the study showed a significant increase in the aspects of creativity and active learning of students. Initially, using conventional learning methods, the level of student participation was only 30%, with only 30% of students actively participating and asking questions. However, after using the experiential learning model, this figure jumped to 85%. This change in values occurs because students are not only placed as spectators in the learning process, but as co-creators who are responsible for their own learning process.